Characterization of a mouse model of islet transplantation using MIN-6 cells. Issue 4 (3rd July 2020) - Sobel, Douglas O.; Ramasubramanian, Barath; Mitnaul, Larry
ABSTRACT: Immortalized beta cells are an abundant source of insulin-producing cells. Although MIN-6 cells have similar characteristics as normal islets in vitro, the in vivo use of MIN-6 cells has not been fully described. This study characterizes in vivo mouse models of MIN-6 transplantation and rejection. Subcutaneous ( sc ) transplantation of MIN-6 cells in either Matrigel or HyStem-C hydrogels reduced blood sugars in nude mice and thus are good matrices for MIN-6 cells in vivo . NOD mice are good transplant recipients since they best rejected MIN-6 cells. MLR responses from BalbC, Black Webster, Swiss Black, C3H, and NOD mice correlated with mean blood glucose response suggesting the importance of allogeneic differences in the rejection of cells. Three days of cyclosporine administration caused no inhibition of MIN-6 cell rejection and 6 days resulted in a transient decrease in blood glucose, while daily administration inhibited rejection long term. Kinetic glucose tolerance (GTT) studies in nude mice demonstrated transplanted MIN-6 cells are close but not as effective as normal islets in controlling blood glucose and blood glucose set point for insulin release in MIN-6 cells decreases to hypoglycemic levels over time. To avoid hypoglycemia, the effect of MIN-6 cell irradiation was assessed. However, irradiation only delayed the development of hypoglycemia, not altering the final glucose set point for insulin release. In conclusion, we have characterized a mouse model for beta-cell transplantation using subcutaneous MIN-6 cells that can be used as a tool to study approaches to mitigate immune rejection.